Intraoperative risk of bleeding and its prevention during transcervical myomectomy. - Kaminsky, V. V.; Dunaevska, V. V.; Medvediev, M. V. (Medicni Perspektivi, 2014)
In this study clinical, functional and morphological assessment of the effectiveness of synthetic analogue of vasopressin (terlipressin) has been made. The aim of the study was to assess study drug prevention efficasy of excessive bleeding during hysteroscopic myomectomy in patients with submucosal uterine leiomyoma. In 19 women with uterine leiomyoma 15 minutes prior to surgery terlipressin was administered in paracervical route in the dosage 0.6 mg in 10 ml of normal saline. In the comparison group, which was also consisted of 19 women in the presence of significant blood loss during myoma resection intravenous oxytocin was used. The use of terlipressin helped to reduce the volume of blood loss during surgery almost by 2 times, reduced the duration of surgery and the risk of postoperative complications. On the basis of the ultrasonic doppler blood flow studies in uterine vessels, morphological and immunohistochemical studies of hemocapillars density in removed myoma nodules it was found that terlipressin contributes significantly to reduction of the number of functioning blood vessels and also to reduction of blood flow in all parts of the vascular system both in uterus and in leiomyoma, whereas oxytocin was not observed to decrease myometrium perfusion. It conclusion the study results showed that terlipressin use is the most effective method of prevention of excessive blood loss during hysteroscopic myoma resection.